A Novel PAX6 Mutation in a Patient with Nonsyndromic Dominant Foveal Hypoplasia and Congenital Nystagmus. - Vezinaw, Chloe M.; Fishman, Gerald A.; John Chiang (Optometry & Visual Performance, 2019)
Background: Foveal hypoplasia is a disorder in which the fovea does not develop normally. It is commonly associated with congenital nystagmus and other developmental conditions, such as aniridia and albinism. Case Report: We examined a 15-year-old female who presented with foveal hypoplasia and congenital nystagmus in the absence of any systemic or anterior segment abnormalities. Genetic testing showed a novel PAX6 missense mutation. Conclusion: This report highlights a case of autosomal dominant, isolated foveal hypoplasia with a novel PAX6 mutation without any anterior segment anomalies.